Planistyczne problemy lokalizacji cmentarza - Rosegnal, Marcin (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Cemetery is a particular spatial structure which requires a specific location enabling realisation of its functions. On one hand, cemetery is a place subject to location requirements defined by law. On the other hand, it contributes to restrictions regarding the possibilities of use of adjacent space. Due to this fact, the legislator predicted the requirement of locating a cemetery in a local spatial plan of development. However, such a form of cemetery location causes a variety of doubts and problems. The aim of this article is the analysis of possibilities of cemetery location taking into account other planning instrument as well as the analysis of mistakes committed during the procedure of outlining a local plan for the needs of cemetery location, which is the issue most often raised by jurisdiction and supervisory bodies
Keywords: cemetery; spatial planning; local plan